AN INTEGRATED FRAMEWORK FOR ASSESSING TECHNOLOGICAL AND INNOVATION READINESS IN IMMERSIVE MARKETING SYSTEMS - Nadiia Artyukhova; Artem Artyukhov (PEOPLE: International Journal of Social Sciences, 2026)
Immersive marketing is emerging as a transformative approach to consumer engagement by creating interactive, multisensory brand experiences. However, immersive marketing initiatives require substantial investment and are characterized by high levels of uncertainty due to their complex and dynamic nature as socio-technical systems. In this context, effective innovation governance becomes critical. The widely applied Technology Readiness Level (TRL) framework provides a structured assessment of technological maturity. Still, it remains limited to technical feasibility and does not capture essential commercial, organizational, and market-related dimensions. This limitation often contributes to the failure of innovations during the transition from development to market deployment, commonly described as the “Valley of Death.” The purpose of this work is to develop a comprehensive governance framework for immersive marketing by integrating Technology Readiness Levels (TRL) with Innovation Readiness Levels (IRL). The study adopts a conceptual and analytical research design based on a systematic synthesis of existing readiness models and their adaptation to the specific characteristics of immersive marketing. Both TRL and IRL nine-level scales are translated into domain-specific criteria, referred to as IM-TRL and IM-IRL, reflecting the technical performance of XR systems alongside market acceptance, organizational capabilities, and business model viability. As a result, an Integrated Readiness Matrix is proposed, enabling the simultaneous evaluation of technological and innovation maturity. The matrix identifies four strategic development quadrants, including two high-risk imbalance scenarios: the “Valley of Death,” where advanced technology lacks commercial readiness, and the “Hype Trap,” where strong market expectations outpace technological maturity. These scenarios highlight the necessity of aligning technical progress with customer readiness and organizational preparedness. The proposed integrated TRL/IRL framework provides innovation managers with a structured tool for reducing investment risks, supporting informed decision-making, and ensuring that immersive marketing solutions evolve in parallel across technical and commercial dimensions. The framework contributes to the advancement of innovation governance in XR-based marketing, offering a foundation for future empirical validation and the development of quantitative customer readiness metrics.